Differentiated thyroid carcinoma presentation may be more aggressive in children and adolescents than in young adults - Giuseppina Zirilli; Laura Cannavò; Francesco Vermiglio; Maria Antonia Violi; Filippo De Luca; Malgorzata Wasniewska (BMC, 2018)
Abstract Background The available studies concerning the influence of age on the phenotypical expression of differentiated thyroid carcinoma (DTC) have hitherto compared DTC presentation either between pre-pubertal and pubertal children or between pediatric patients and aged adults; aim of this study was to ascertain for the first time whether presentation of DTC may significantly vary according to age, even within a peculiar study population covering only young patients aged less than 30 years. Methods The main clinical, biochemical and pathologic data at DTC diagnosis were retrospectively recorded in 2 selected cohorts including, respectively, 18 children and adolescents aged less than 18 years (Group A) or 45 young adults aged between 20 and 29.8 years (Group B). Results The statistical distribution of DTC cases in the different age ranges was found to progressively increase with increasing age; furthermore, the patients of Group A exhibited at diagnosis a more severe clinical involvement and a higher rate of extra-regional metastases; finally, also the association with both autoimmune thyroid diseases (AITDs) and a biochemical hypothyroid pattern was more common in Group A patients. Conclusions In a study population younger than 30 years: a) the risk of developing DTC increases with age, achieving its zenith during the 3rd decade of life; b) clinical presentation is more severe in children and adolescents younger than 18 years than in the patients aged between 20 and 30; c) in the cohort of children and adolescents DTC is more often associated with AITDs, which might play some role in conditioning the more aggressive phenotypical presentation of DTC in this patient group.